PENGARUH JOB INSECURITY DAN STRES KERJA KARYAWAN TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN PT. INDOMARCO ADI PRIMA CABANG BENGKULU - Sari, Lisa Pusfita; Onsardi, Onsardi; Wahyudi, Dedy (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
The purpose of this study is to analyze the influence of Job Insecurity (X₁) and Work Stress (X₂) on Organizational Commitment (Y) in employees of PT Indomarco Adi Prima Bengkulu Branch. The type of research uses a descriptive quantitative approach with a survey method. The research sample consisted of the entire employee population (42 people) through total sampling techniques. Data were collected through questionnaires, observations, and interviews, and then analyzed by multiple linear regression using SPSS. The results of the study showed that Job Insecurity had a significant effect on Organizational Commitment (tcal = 5,040 > ttₐbₑl = 1,684; Sig. 0.000 < 0.05). Work Stress had a significant effect (tcount = 13,047 > ttₐbₑl = 1,684; Sig. 0.000 < 0.05). Job Insecurity and Work Stress together have a significant effect on Organizational Commitment (Fcal = 95,168 > Ftₐbₑl = 3.24; Sig. 0.000 < 0.05). The Coefficient of Determination (R²) of 0.830 indicates that 83% of the variation in Organizational Commitment is explained by Job Insecurity and Work Stress, while 17% is influenced by other variables outside the model. This research shows that the increase in Job Insecurity and Work Stress significantly decreases Organizational Commitment. The practical implication is that companies need to manage job insecurity and workloads to strengthen employee loyalty. Keywords: Job Insecurity, Work Stress, Organizational Commitment